2002
DOI: 10.1073/pnas.262591699
|View full text |Cite
|
Sign up to set email alerts
|

Excision of misincorporated ribonucleotides in DNA by RNase H (type 2) and FEN-1 in cell-free extracts

Abstract: Misincorporated ribonucleotides in DNA will cause DNA backbone distortion and may be targeted by DNA repair enzymes. Using double-stranded oligonucleotide probes containing a single ribose, we demonstrate a robust activity in human, yeast, and Escherichia coli cell-free extracts that nicks 5 of the ribose. The human and yeast extracts also make a subsequent cut 3 of the ribonucleotide releasing a ribonucleotide monophosphate. The resulting 1-nt gap is an ideal substrate for polymerase and ligase to complete a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(173 citation statements)
references
References 28 publications
5
167
0
Order By: Relevance
“…Although the exact in vivo substrates of these nucleases remain to be identified, they are thought to act on RNA:DNA hybrids such as those arising during nuclear DNA replication and R‐loop formation (Cerritelli & Crouch, 2009). Unlike RNase H1, RNase H2 also cleaves and initiates the removal of single ribonucleotides embedded in DNA (Eder et al , 1993; Rydberg & Game, 2002), a process known as ribonucleotide excision repair (RER) (Sparks et al , 2012). RNase H2 is essential for mammalian genome stability, with complete loss of RNase H2 resulting in embryonic lethality (Reijns et al , 2012; Hiller et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact in vivo substrates of these nucleases remain to be identified, they are thought to act on RNA:DNA hybrids such as those arising during nuclear DNA replication and R‐loop formation (Cerritelli & Crouch, 2009). Unlike RNase H1, RNase H2 also cleaves and initiates the removal of single ribonucleotides embedded in DNA (Eder et al , 1993; Rydberg & Game, 2002), a process known as ribonucleotide excision repair (RER) (Sparks et al , 2012). RNase H2 is essential for mammalian genome stability, with complete loss of RNase H2 resulting in embryonic lethality (Reijns et al , 2012; Hiller et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, only RNase HII is capable of removing single RNA from DNA-RNA/DNA-DNA hybrids, such as those produced when RNA is misincorporated into DNA (Haruki et al, 2002;Rydberg & Game, 2002). A recent extensive phylogenetic analysis of 353 prokaryotic genomes revealed that the RNase H group has evolved in such a way that genes encoding RNase HI and RNase HIII are inherited in a mutually exclusive manner, which may be attributed to the functional redundancy of the two enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rad27D, which affects the processing of RNA primers in Okazaki fragments, the increase in slippage mutations is expected based on the fact that there are more rNMPs remaining in the DNA of mutant cells. 4 Accordingly, the double mutant rnh202D rad27D displayed a synergistic increase in slippage mutations, indicative of overlap in function in removing rNMPs from DNA. The pol3-01 mutant gave an increase in mutation slippage in an RNaseH2-proficient strain, confirming the role of the Pol3 editing function in mutation prevention.…”
Section: Dna Repair Nucleasesmentioning
confidence: 98%
“…Mutation rates for the (AG) 4 slippage reporter and Can r were determined by the Lea and Coulson median method as previously described. 1,2,18 For the (AG) 4 slippage reporter, single colonies were inoculated into 5 mL YPD and grown for 2 d at 30 C, washed and resuspended in 1 mL H 2 O.…”
Section: Determination Of Mutation Ratesmentioning
confidence: 99%
See 1 more Smart Citation